Average Error: 28.5 → 0.5
Time: 17.7s
Precision: 64
$\tan \left(x + 1\right)$
$\frac{\tan x + \tan 1}{\log \left(e^{1 - \tan 1 \cdot \tan x}\right)}$
\tan \left(x + 1\right)
\frac{\tan x + \tan 1}{\log \left(e^{1 - \tan 1 \cdot \tan x}\right)}
double f(double x) {
double r58469127 = x;
double r58469128 = 1.0;
double r58469129 = r58469127 + r58469128;
double r58469130 = tan(r58469129);
return r58469130;
}


double f(double x) {
double r58469131 = x;
double r58469132 = tan(r58469131);
double r58469133 = 1.0;
double r58469134 = tan(r58469133);
double r58469135 = r58469132 + r58469134;
double r58469136 = r58469134 * r58469132;
double r58469137 = r58469133 - r58469136;
double r58469138 = exp(r58469137);
double r58469139 = log(r58469138);
double r58469140 = r58469135 / r58469139;
return r58469140;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 28.5

$\tan \left(x + 1\right)$
2. Using strategy rm
3. Applied tan-sum0.4

$\leadsto \color{blue}{\frac{\tan x + \tan 1}{1 - \tan x \cdot \tan 1}}$
4. Using strategy rm
$\leadsto \frac{\tan x + \tan 1}{\color{blue}{\log \left(e^{1 - \tan x \cdot \tan 1}\right)}}$
$\leadsto \frac{\tan x + \tan 1}{\log \left(e^{1 - \tan 1 \cdot \tan x}\right)}$
herbie shell --seed 1